An in vitro study to evaluate and compare the surface roughness in heat-cured denture-based resin and injection-molded resin system as affected by two commercially available denture cleansers - Tripathi, Pankaj (J Indian Prosthodont Soc, 2018)
BACKGROUND: Denture hygiene is of utmost importance to maintain the dentures as well as the underlying tissues in appropriate health. Various denture cleansers as well as denture-based materials have evolved in the market; however, the effect of denture cleansers on different types of denture-based materials has not been very well documented. AIM: The purpose of this in vitro study was to evaluate and compare the surface roughness in heat-cured denture-based resin and injection-molded resin system as affected by two commercially available denture cleansers for a period of 15, 30, and 45 days. METHODOLOGY: A standardized metal die was fabricated to make 120 denture-based resin discs of uniform dimensions. The samples of heat-cured denture-based resin and injection-molded thermoplastic denture-based resin were immersed in the two denture cleansing solutions for a period of 15, 30, and 45 days, respectively. The surface roughness was evaluated by surface profilometer TR200. The data were subjected to statistical analysis and the comparison of quantitative data was done using unpaired t-test and repeated-measures ANOVA test. RESULTS: The surface roughness values (Ra) of heat cured denture base resin samples when immersed in two denture cleansers were 0.22 μm at 0 days, 0.27 and 0.29 μm at 15 days, 0.29 and 0.31 μm at 30 days, 0.30 and 0.31 μm at 45 days whereas for injection moulded samples surface roughness values were 1.31 & 1.27 μm at 0 days, 1.46 & 1.66 μm at 15 days, 1.50 & 1.69 μm at 30 days, and 1.50 & 1.69 μm at 45 days. CONCLUSION: The surface roughness (Ra) increased significantly in injection-molded polyamide denture-based resin samples when immersed in both the denture cleansers. Whereas, heat-cured denture-based resin samples did not reveal any significant surface changes at the various time intervals. Hence, the use of denture cleansers is questionable in thermoplastic resins.